Si Tak-tu - Gatmaitan, Luis P. (Chikiting books, 2013)
"Tak-Tu? Who is Tak-Tu? Gilbert asked himself when he heard other children mention the name, which he had never heard of before. To his surprise,, they tell him that he is Tak-Tu. What does Tak-Tu mean? Why do Gilbert's playmates call him that? Does it have something to do with the strange smell that seems to appear whenever he is around?"